The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.6063/motricidade.10058
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Developmental Coordination Disorder signs in children 5 to 14 years in São Carlos

Abstract: This study aimed to identify the prevalence of Developmental Coordination Disorder (DCD) in children aged 5-14 years, enrolled in public preschools and elementary schools in São Carlos -SP. There were 130 participating families. Instruments were: Developmental Coordination Disorder Questionnaire -Brazil (DCDQ -Brazil), Brazil criteria and a questionnaire for the characterization of children. The prevalence of DCD found was 30%, which is overestimated when compared to data found in much of the literature, justi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
2
3
0
1
Order By: Relevance
“…Tsiotra et al (2006) concluded that lifestyle differences, such as neighbourhood, environment and culture, should be taken into account when identifying motor skill difficulties or possible DCD. Barba et al (2017) and Valentini et al (2015) supported the argument of Tsiotra et al (2006), confirming that a low socio-economic environment and family status are risk factors for DCD and increase the risk for motor skill difficulties.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Tsiotra et al (2006) concluded that lifestyle differences, such as neighbourhood, environment and culture, should be taken into account when identifying motor skill difficulties or possible DCD. Barba et al (2017) and Valentini et al (2015) supported the argument of Tsiotra et al (2006), confirming that a low socio-economic environment and family status are risk factors for DCD and increase the risk for motor skill difficulties.…”
Section: Discussionsupporting
confidence: 55%
“…However, the http://www.sajce.co.za Open Access researcher was not able to involve a medical doctor to diagnose general medical conditions (criterion C) in the participating learners in this study. As criteria B and C were not fully met, it could not be alluded that the learner had DCD (Barba et al 2017), and therefore the learners were referred to as having possible DCD if they fell below the 16th percentile in the MABC-2 performance test. Further exclusion criteria comprised (1) learners falling outside the age range of 6-8 years and (2) parents indicating that they were relocating.…”
Section: Participantsmentioning
confidence: 99%
“…In India, Deshmukh et al (2021) surveyed a total 716 children aged 5-10 years and observed that 23.9% of children had signs of suspected DCD according to the developmental coordination disorder questionnaire 2007 (Wilson et al, 2007). In similar studies conducted by Della Barba et al (2017) and Delgado-Lobete et al (2019), the prevalence of suspected DCD in 5-14 year old children in Brazil and in 6-12 years old children in Spain were found to be 30% and 12.5%, respectively.…”
Section: Introductionsupporting
confidence: 53%
“…Studies identify the relationship between DCD and socioeconomic status (Della Barba et al, 2017;Santos et al, 2015). Children from private schools performed better on the motor test (Cardoso et al, 2014), as well as having fewer reports of motor coordination problems by teachers compared to those from public schools (Magalhães et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%